ECOLOGICAL CHALLENGES IN THE DEVELOPMENT OF GEORGIA ENERGY (Globalization and Business, 2018)
The  article  views  environmental  protection  issues  in the energy sector of Georgia. Trends of developing energy complex are discussed and assessed envisaging ecological requirements.  It  is  indicated  that  energy  complex  is  the most polluting one among the fields of material production. Focus in made on ecological problems of the land, including cultivable ones, water, climate and other fields. The Georgian experience  is  presented  in  respect  with  meeting  these challenges. At the end, views are given for improving the situation. Points to be stressed are:Rational production and usage for energy resources, creation  of  energy  recourse-conserving,  low  waste  or  no waste  environmentally  clean  technologies,  reduction  of emissions,  and  thermal  gases  polluting  an  environment, decrease of harmful action of industrial and other waste and waste utilization;Construction   and   reconstruction   of   systems   of protection  of  environment,  including  increase  of  rates  of filtration  and  neutralization  of  natural  substances  in  the exhaust  gases,  waste  water,  cleaning  of  ground  polluted and damaged during construction and operation of energy facilities, and also usage of industrial waste as secondary raw material;Provision of economic incentives of rational use of casing-head gases, suppression of practice of their burning in their torches (first of all at the experience of creation of economically favorable conditions for use of such gases);Introduction of environmentally clean technologies of coal burning in thermal power stations and other enterprises, as a condition of coal use prospects;Improvement of coal fuel quality (including its enrichment, processing, bracketing etc.);Usage of mine methane;Growth  of  production  of  high-quality  engine  fuels appropriate   to   the   European   standards,   improved   for conformity  with  the  requirements  of  the  advanced  legal base for polluting substances and exhaust gases emitted as a result of oil products combustion;Development   and   realization   of   the   programs of   minimization   of   environmental   damage   caused   by construction and functioning of hydroelectric power stations;Organization of works of certification of environmentprotection technologies and means;Organization of experts training working in a sphere of an environmental protection.